BELBIC : BELBIC, soft computing, fuzzy logic, evolutionary algorithm, neural network, genetic algorithm, caro Lucas, amygdala, orbitofrontal cortex, thalamus, scientific modelling - Miller, Frederic P.; Vandome, Agnes F.; McBrewster, John (Mauritius : Alphascript Publishing, 2010)
PSZJBL